SOSIALISASI PEMANFAATAN APLIKASI GRATIS (MYMONEY) UNTUK PENCATATAN KEUANGAN SEDERHANA BAGI SANTRI DI PONDOK PESANTREN TAHFIDZ AL-QUR’AN BINA ATTAUFIQ ATAP YATIM - Anisah Dwi Putri; Adinda Salsabila; Selia Ritandi; Rizko Fadli Anhari; Juitania (Jurnal Abdi Citra, 2026)
This community service program aims to improve financial literacy among teenagers through the dissemination of simple financial management based on the free MyMoney application. Amidst low levels of financial literacy among Indonesian teenagers, which triggers consumptive behavior, financial digitization has become a practical solution for building effective transaction recording habits. The activity was carried out at the Tahfidz Al-Quran Bina At-Taufiq Islamic Boarding School at the junior high school level, involving 27 students using a practical approach-based community service method. The community service method used observation and interviews to identify limitations in cell phone access, disseminate financial management material, and provide interactive practice assistance using MyMoney application features such as Account, Records, Budgets, Categories, and Analysis. This approach was adapted to the conditions of the boarding school through manual recording before digital input. The results of the community service showed that the activities were successful, with students understanding income and expenditure management in real-time and visually through the application's graphics. This program succeeded in fostering positive financial literacy motivation and recommended the integration of simple financial applications in youth education to support long-term financial stability.